Business Ethics in Theory and Practice
VIII, 248 p.
Keywords: This book originated in a symposium on business ethics that took place in the Faculty of Commerce at the University of Canterbury in September of 1997. Professor Werhane, who was a visiting Erskine Fellow, provided the keynote address, and many of the papers in this collection were originally presented at this symposium. We are grateful to Kluwer Publishers for the opportunity to publish these essays in their series on International Business Ethics. We want to thank the Olsson Center for Applied Ethics at the Darden School, University of Virginia, and the Erskine Trust and the Department of Management at the University of Canterbury for their support of Professor Werhane's fellowship, research for this text, and funding for its production. We especially want to thank Lisa Spiro, who copy-edited and prepared the manuscript for publication. INTRODUCTION AND OVERVIEW This book originated in a symposium on business ethics that took place in the faculty of commerce, at the University of Canterbury, in September 1997. Professor Werhane, who was a visiting Erskine Fellow, provided the keynote address. Contributions to the proceedings were. inter-disciplinary, spanning theory and practice. Subsequent contributions were obtained from within New Zealand and from Asia. The book starts off on rather a pessimistic note: the new managerialism (the kind of thing Scott Adams jokes about in the world-famous Dilbert cartoons) is economically suspect and psychologically damaging.